INCIDENCE OF URINARY TRACT INFECTION AFTER CYSTOGRAPHY - Joana Sousa Martins; Margarida Pinto; Manuela Braga; Paulo Calhau (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: Cystography an invasive procedure with potential complications such as urinary infection (UI). There are few studies about the incidence of complications associated with this procedure. The purpose of this study is to evaluate the incidence of post-cystography urinary infection (UI.). Methods: Retrospective study with a review of clinical records of patients under 15 years of age, followed in this hospital, who underwent cystography (radiologic or indirect radionuclide) between 2009 and 2018. Post-cystography UI was defined when it occurred until seven days after the procedure. Descriptive and nonparametric statistics were applied to assess possible predictive factors related with post-cystography UI. Results: In the study period, 531 cystograms were undertaken (55% indirect radionuclide and 45% radiologic). The mean age at the procedure was 11.5 months; 62% were boys. Every patient had a previous negative urine culture; 50% were under antibiotic prophylaxis at the time of the procedure. The most common indication for the procedure was the post-natal study of congenital hydronephrosis/other nephrological malformation (53%), followed by the study of febrile UI (31%). Vesicoureteral reflux (VUR) was diagnosed in 40% of procedures. Post-cystography UI occurred in 23 cases (incidence of 4.3%). The most frequent microorganism was E. coli (52%). The presence of VUR was significantly associated with the occurrence of post-cystography IU. Conclusions: The incidence of post-cystography UI was low in our sample. The presence of VUR was significantly associated with the occurrence of post-cystography UI. The authors highlight the importance of an adequate catheterization technique and the need for clinical surveillance after the procedure.